Soil survey using geostatistics in an agricultural experimental area in Petrolina, Pernambuco state, Brazil - Silva, Kátia Araújo da; Rodrigues, Marcos Sales; Cunha, Jailson Cavalcante; Alves, David Castro; Freitas, Helder Ribeiro; Lima, Augusto Miguel Nascimento (Comunicata Scientiae, 2017)
Due to the importance of accurate information on soils for agricultural production, quantitative techniques to estimate classes and/or soil properties have been developed to increase these maps quality. This manuscript was developed to map soils of an agronomic experimental area using geostatistical tools to assist in the allocation and management of experiments. The study area is located in an agricultural experimental area of Federal University of São Francisco Valley, Petrolina County, Pernambuco state, Brazil. Mapping the agricultural area consisted of a soil profile and a sampling grid with 51 georeferenced points. At these points the soil samples were collected at 0-0.2 m and 0.4-0.6 m soil depths that corresponded to A and B soil horizons, respectively. Soil samples were evaluated for physical (soil texture) and chemical analysis. The spatial dependence of soil attributes was described using semivariograms and maps were interpolated by ordinary kriging. The results showed that the predominant soils in the area were Ultisol with a cohesive eutrophic horizon, Ultisol with a cohesive dystrophic horizon, and Ultisol with a sandy cohesive dystrophic horizon. The geostatistical proved to be an important tool supporting the ultra-detailed pedological mapping of the agricultural research area.